A baseline for the monitoring of Mediterranean upper bathyal biogenic reefs within the marine strategy framework directive objectives. (April 2023) - Angiolillo, Michela; Bo, Marzia; Toma, Margherita; Giusti, Michela; Salvati, Eva; Giova, Antonio; Lagudi, Antonio; Rossi, Lorenzo; Collina, Matteo; Bruno, Fabio; Canese, Simonepietro; Tunesi, Leonardo
Abstract: The Marine Strategy Framework Directive (MSFD, 2008/56/EC ) was adopted to achieve a Good Environmental Status (GES) in the EU's marine waters and to protect resources and ecosystem services, including the deep-sea waters and seafloor. The deep sea (below 200 m) is the largest biome on Earth, and its biodiversity plays a key role, despite being strongly threatened by several anthropogenic stressors, potentially affecting some ecosystem functions. Among the main deep-sea structuring species, the habitat-forming cold-water corals (CWCs) are known to form Vulnerable Marine Ecosystems (VMEs). In the Mediterranean Sea, in the last two decades, a significant effort has been devoted to unveiling the distribution, extension and ecological role of scleractinian CWCs ( Madrepora oculata and Desmophyllum pertusum ), but quantitative data on their conservation status are very limited. Because of their ecological importance and vulnerability, Italy has extended the implementation of the MSFD to the deep sea, carrying out specific monitoring programmes on these scleractinian CWCs. In this regard, this study established, for the first time, an extensive standardized baseline for national monitoring programmes focusing on two recently discovered upper bathyal areas dominated by scleractinian CWCs (Dohrn Canyon and Corsica Channel). The goal was to evaluate the ecological status of the bathyal biogenic reefs using traditional diversity and impact variables as well as the innovative photogrammetry tool. In both areas, the investigations have increased the knowledge about the extent of the habitat and new CWC assemblages in good health conditions were discovered. The pressure extent is limited with respect to the total extent of the CWC habitat, accounting for approximately 32% and 63% of the fishing- related items entangled on structuring species. The photogrammetric approach showed a deviation of about 33% in the measurement of the population size structures. Moreover, the use of a standardized operative protocol has been proposed to obtain reliable, coherent, and comparable data for future monitoring activities. This approach improved scientific knowledge for the two studied areas and it is pivotal in defining long-term monitoring activities useful to assess the effectiveness of specific protection measures, for these VMEs. Highlights: The Good Environmental Status of two upper bathyal biogenic reefs was assessed. Conventional imaging and innovative photogrammetry analysis were applied. A monitoring protocol under Marine Strategy Framework Directive was proposed. No extensive habitat destruction threatening environmental integrity was observed. The information collected will be used as baseline for future monitoring cycles.